Estimating deterministically time-varying variances in regression models - George Kapetanios (Queen Mary University of London, Department of Economics, 2005)
The problem of structural change justifiably attracts considerable attention in econometrics. A number of different paradigms have been adopted ranging from structural breaks which are sudden and rare to time varying coefficient models which exhibit structural change more frequently and continuously. This paper is concerned with parametric econometric models whose coefficients change deterministically and smoothly over time. In particular we provide a new estimator for unconditional time varying variances in regression models. A small Monte Carlo study indicates that the method works reasonably well for moderately large sample sizes.
Keywords: C10; C14; 330; Structural change; Non-stationarity; Deterministic time-variation; Strukturbruch; Regression; Sch\~AƒÂtztheorie